An investigation into the effect of electrode type and stimulation parameters on FES-induced dynamic movement in the presence of muscle fatigue for a voltage-controlled stimulator. (30th June 2019) - Stewart, Ashley M.; Pretty, Christopher G.; Chen, XiaoQi
Abstract: Functional Electrical Stimulation (FES) is very useful in Stroke Rehabilitation for rebuilding muscle strength, both in a clinical setting and for home-based rehabilitation, however it is limited in its usage due to the resulting FES-induced muscle fatigue, as well as a large variation in muscle response. This paper compares the effectiveness of e-textile electrodes with conventional hydrogel electrodes at a range of stimulation parameters. The e-textiles produced a stronger response at a lower voltage than the hydrogels (3–4 V difference for a stimulation intensity voltage range of 8–22 V) and offer more consistency across different FES sessions. A simple model was then developed which relates the variation of the stimulation parameters (voltage, pulse-width, and frequency) to a change in angle for the elbow joint (Bicep muscle) using the e-textile electrodes. Step responses for various combinations of FES parameters were measured for 8 different healthy subjects for a total of fifty 10 min long tests. Overall the model produced good predictions of the arm response and it was found that the model was more accurate and consistent for combinational parameter steps than for individual parameter steps. The R 2 value for the measured step change compared with the predicted step change for FES-induced contractions for all step types and subjects combined was 0.76 for one of the methods using the model